Decision Making System for Selection of Students for Achievement Scholarships at SMA Negeri 14 Medan - Sitohang, Norenta (Cattleya Darmaya Fortuna, 2023)
This research explains the problem of decision making in selecting students for achievement scholarships to support student achievement at SMA Negeri 14 Medan. Problem solving uses a qualitative research method which seeks to obtain information about the object being researched according to the reality of students at school by using the interview method, namely collecting data by interviewing directly. The research was conducted at SMA Negeri 14 Medan, namely Jl. East Ujung Students, Binjai Village, Medan District, Medan City. The achievement of the aim of this research is to describe and explain to students and educational institutions as a contribution to thinking in fostering educational values ​​and deciding which outstanding students receive scholarships